Turkey: Dynamic efficiency considerations in merger control analyses - Gürkaynak, G.; Koz, Ç.; Topaloğlu, S.N. (Institute of Competition Law, 2018)
La destination finale et le but ultime mis en avant dans notre article est la nécessité pour l'Autorité de la Concurrence Turque de prendre en considération l'innovation dans son contrôle des concentrations en adoptant des outils dynamiques. Ainsi, nous soutenons que l'Autorité de la Concurrence Turque devrait "tracer son parcours à Ithaca" et viser à atteindre "l'état idéal" dans son application des règles de la concurrence. L'Autorité de la Concurrence Turque devra tenir compte du fait que, indépendamment de la longueur, de la difficulté et des épreuves de ce voyage, chaque pas suivi dans ce chemin la rapprochera de l'Ithaca et l'aidera à atteindre les objectifs fondamentaux de l'application des règles de concurrence. Sans entreprendre cet aventureux, difficile et long voyage, il ne sera pas possible de parvenir à la destination finale. © 2018 Institute of Competition Law.The final destination and the ultimate goal that we put forth in our article is that the Turkish Competition Board should include innovation considerations in its merger control analyses by employing dynamic tools. Accordingly, we contend that the Turkish Competition Board should "set its course to Ithaka" and aim to reach its "ideal state" in its enforcement of competition rules. The Turkish Competition Board should bear in mind that, regardless of how long, arduous and full of hardship the journey may be, each step taken on this path brings it closer to Ithaka and helps it to achieve the fundamental goals of competition enforcement. Without undertaking this adventurous, challenging and lengthy voyage, it is not possible to reach the final destination. © 2018 Institute of Competition Law.
Keywords: Competition Policy; Economic Analysis; Economic Efficiency; International; Merger Clearance (Phase I); Merger Clearance (Phase Iı); Turkey